Perianal ulcerative tuberculosis: a case report - Lao, Weifeng; Mao, Weifang (Journal of the Pakistan Medical Association, 2022)
Perianal tuberculosis (TB) is an extremely rare form of mycobacterial infection, in which the anal mucocutaneous junction becomes infected by autoinoculation from an active draining gastrointestinal tract infection. The case of a 73-year-old immunocompetent male patient, who came in with a refractory perianal ulcer is presented. The patient had no history of TB and his lab tests for TB were all negative. A chest X-ray showed streak and nodular opacities in both upper lungs. The ulcer was biopsied twice and a diagnosis of TB was finally rendered by histological examination with confirmatory Polymerase chain reaction (PCR). The lesion was finally cured by intensive anti-TB treatment. Perianal TB needs to be excluded in patients with a refractory perianal ulcer, including immunocompetent cases without TB history. Biopsies and microbiological tests should be performed for any suspicious lesion and repeated if there is high clinical concern. ---Continue